Preparation and properties of lightweight and high-strength building ceramsites with oil-based drilling cuttings pyrolysis residues - Wang, Hongjuan; Li, Jing; Lin, Dong; Jiang, Guobing; Zhao, Liang; Yu, Jinlei; Meng, Tian; Huang, Xinyu; Liu, Hongwu; Yang, Yuanyi (Frontiers in Materials, 2023)
With the continuing advancement in China's exploration and development technologies of shale gas resources, there was a significant increase in shale gas oilbased drilling cuttings. In this paper, oil-based drilling cutting pyrolysis residues (ODCPRs) was used as the main raw material for preparing lightweight and highstrength building ceramsites to eliminate the environmental risks and recycle industrial waste. Firstly, orthogonal experiments were used to study the influences of raw material composition, preheating temperature, preheating time, sintering temperature, and sintering time on the properties of building ceramsites. From the results, the sintering temperature and the content of ODCPRs were discovered to be the key factors affecting the sintering process of ceramsites. Secondly, the influences of sintering temperature and heating rate on the properties of building ceramistes were further explored to find the optimum sintering conditions. When the content of ODCPRs in the ceramsite was set to be 50%, the obtained building ceramsites presented excellent properties with particle compressive strength of 6.31 MPa, bulk density of 575.11 kg/m 3 , apparent density of 1097.24 kg/m 3 , and the water absorption of 1.89%. Finally, XRD, SEM, TG-DSC, and heavy metal leaching experiments were comprehensively conducted to analyze the composition structure variation and sintering mechanism of the building ceramisite. This paper presents an approach for the recycling, utilization, and disposal of oil-based drilling cuttings in the oil field waste management.